A Comparative Study to Assess the Mental Health Problems, Quality of Life, Work Ability and Social Adjustments Among OST and Non-OST Drug Users in Chandigarh. Issue 4 (October 2022) - Kumar, Pardeep; Sharma, Sunita; Saini, Sushma Kumari; Mittal, Sandeep; Gupta, Vanita
Introduction: Injectable drug use is a cause of disease burden and a contributor to blood-borne virus transmission and health-related problems. It is one of the serious problems of our country. The best suitable strategy of treatment for opioid dependence is 'opioid substitution therapy' (OST). It is beneficial for the injectable drug users (IDUs) in reduction in the behaviour of injecting and opioid use, which helps in reducing criminal activities, domestic violence, enhancing ties within the family and improving productivity. Objective: To assess the mental health problems, quality of life, work ability and social adjustability among OST and non-OST IDUs. Materials and Methods: The descriptive study was conducted among 100 male IDUs (50 in the OST group and 50 in the non-OST group), registered with the two selected non-governmental organizations (NGOs) of Chandigarh selected by using the consecutive sampling technique. The OST group was contacted during their visit to the centre for receiving the daily dose of OST, while the non-OST group was contacted during their visit to the NGO centres for getting fresh syringes in exchange with used syringes under the syringe exchange programme. The data were collected by interviewing the study subjects by using the interview schedule comprising of the (a) socio-demographic profile, (b) health problems, (c) substance-use-related problems scale, (d) work ability and social adjustability scale, (e) the depression, anxiety and stress scale-21 and (f) World Health Organization Quality-of-Life BREF (WHOQOL BREF) Scale. All the tools were standardized and available in the open domain. Results: The study subjects were in the age group of 18–58 years with the mean age of 27.52 ± 6.67 years. Significantly lesser problems in the OST group study participants related to health, occupation, finance, legal, family, marital and social status were reported than those in the non-OST group participants ( t -test, p < 0.01). A significantly higher percentage of the study participants in the non-OST group had depression, anxiety and stress than that in the OST group. Quality of life of IDUs in the OST group was significantly better than that of IDUs in the non-OST group, as per the WHOQOL BREF Scale (Mann–Whitney U test, p < 0.05). Conclusion: IDUs on OST therapy (OST group) were having lesser problems in the area of health (physical and mental), occupational, financial, legal, family, marital, social and better quality of life than those in the non-OST group.